Pengalaman Jurnalis Perempuan Di Media Penyiaran Islam: Studi Fenomenologi Atas Kekerasan Dan Pelecehan Seksual - Mutia Tanseba Andani (Journal of Innovative and Creativity, 2025)
This study examines the high prevalence of violence and sexual harassment against female journalists in Islamic broadcast media, which according to an AJI–PR2Media survey (2022/23), was experienced by 82% of respondents. The lack of institutional response, patriarchal culture, and pressure from religious norms increase vulnerability and silence victims. The research problem is formulated as follows: How do female journalists in Islamic broadcast media experience sexual violence and harassment, and what meaning do they give to these experiences? This qualitative descriptive study uses a phenomenological approach with the Feminist Standpoint theory by Sandra Harding and Dorothy Smith. Data were obtained through a literature review of relevant journal articles and books, analyzed holistically to explore victims' subjective meanings. The results show that forms of violence include verbal harassment, sexual staring, unauthorized physical touching, and online harassment, often disguised as moral justification or religious language. Barriers to reporting are influenced by social stigma, career risks, and the lack of victim-friendly standard operating procedures. The meanings that emerged included moral-professional tests, awareness of structural vulnerability, advocacy triggers, and spiritual resilience, where Islamic identity became a source of moral strength to reject harassment while simultaneously encouraging internal policy changes. Keywords: Female Journalists, Islamic Broadcasting Media, Sexual Violence, Phenomenology, Feminist Standpoint Theory.